Pemberdayaan Guru MTs Swasta Nurul Qur’an dalam Mengembangkan Media Belajar dari Kantong Plastik - Zuraini,; Eli Nofriati,; Rahmi Hayati,; Husnidar,; Faizah M. Nur, (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2025)
The problem faced by the teachers at the MTsS Nurul Qur’an Bireuen Districts, Aceh is lack of the teachers’ knowledge and creativity in developing the teaching media as the tools of teaching learning process in the classroom. Based on the problem above, the community service aims to give the new knowledge and experience for the teachers at MTsS Nurul Qur’an Bireuen Districts in developing the teaching media by their creativity using the plastic bag. The method used in this community service was giving training to the teachers which come from the different subjects. The training was done in two sessions for a day. In this activity, the teachers were trained to make the teaching media from the used plastic bag. The result of the community service activity was done successfully and the teachers got the new knowledge in creating the teaching media.